Bacterial profile and antimicrobial susceptibility patterns of isolates from burn wound infection at tertiary care hospital - Nisha Devi; Manjula Vagarali; Lokjan Singh; Anil Kumar; Nishant Rai; Manjusha Tyagi (Environment Conservation Journal)
The most prevalent pathogens depend on the burn wound site, which reflects the hospital's nosocomial pathogens. Considering that burn wound infections, both endogenous and exogenous, continue to be the leading cause of disability and mortality across all age groups and in both developed and developing nations, The antibiotic-resistant pattern of aerobic bacteria represents a vulnerable site for opportunistic colonization. The present study aimed at bacterial profiling and antimicrobial susceptibility patterns of isolates from burn wound infection in a tertiary care hospital. It was reported that thermal burns were 49.1%, electrical injuries were 37.4%, and scald burns were 13.5%. Among these, 38 (76%) were recognized as Gram-negative rods, and 12 (24%) were identified as Gram-positive cocci. Out of 38 pathogenic Gram-negative rods, 18 (47.36%) were Klebsiella pneumoniae, 10 (26.31%) were Pseudomonas aeruginosa, 4 (10.52%) were Acinetobacter species, 5 (13.15%) were Escherichia coli, and 1 (2.63%) was Citrobacter freundii. Out of 12 (24%) Gram-positive cocci, 9 (75%) coagulase. Negative Staphylococcus aureus (CONS), 2 (16.66%), Staphylococcus aureus, 1 (8.33%), and Enterococcus species were identified. In contrast, Staphylococcus aureus was 2 (4.4%) and Enterococcus species was 1 (2.2%). Staphylococcus aureus showed maximum sensitivity to chloramphenicol (C), clindamycin (CD), and vancomycin (VA). Chloramphenicol (23.9%) and tetracycline (19.5%) were effective drugs against Gram-negative organisms. The investigation revealed a wide variety of bacteria with markedly different resistance profiles, including both Gram-positive and Gram-negative organisms. Because of this intricacy, specific antimicrobial medications, depending on the features of each illness, are required.